Alpha-band power increases in posterior brain regions in attention deficit hyperactivity disorder after digital cognitive stimulation treatment: randomized controlled study. Issue 2 (17th February 2022) - de Ramón, Ignacio; Pacios, Javier; Medina, Rafael; Bouhaben, Jaime; Cuesta, Pablo; Antón-Toro, Luis; Quintero, Javier; Quiroga, Antoni Ramos; Maestú, Fernando
Abstract: The changes triggered by pharmacological treatments in resting-state alpha-band (8–14 Hz) oscillations have been widely studied in attention deficit hyperactivity disorder. However, to date, there has been no evidence regarding the possible changes in cognitive stimulation treatments on these oscillations. This paper sets out to verify whether cognitive stimulation treatments based on progressive increases in cognitive load can be effective in triggering changes in alpha-band power in attention deficit hyperactivity disorder. With this objective, we compared a cognitive stimulation treatment ( n  = 12) to a placebo treatment ( n  = 14) for 12 weeks (36 sessions of 15 min) in child patients (8–11 years old) with attention deficit hyperactivity disorder. Two magnetoencephalographic recordings were acquired for all participants. In order to extract the areas with changes in alpha power between both magnetoencephalographic recordings, the differences in the power ratio (pre/post-condition) were calculated using an analysis of covariance test adjusted for the age variable. The results show an increase in the post-treatment alpha power in the experimental group versus the placebo group ( P  < 0.01) in posterior regions. In addition, these changes were related to measures of attention, working memory and flexibility. The results seem to indicate that cognitive stimulation treatment based on progressive increases in cognitive load triggers alpha-band power changes in children diagnosed with attention deficit hyperactivity disorder in the direction of their peers without this disorder. Abstract : The magnetoencephalography study by Medina et al. reports a game-like cognitive intervention for children with attention deficit hyperactivity disorder that can induce an enhancement in alpha power over the posterior regions of the brain. Moreover, this alpha power enhancement negatively correlates with attention deficit symptoms. Graphical Abstract: Graphical Abstract